2018
DOI: 10.1298/ptr.r0002
|View full text |Cite
|
Sign up to set email alerts
|

Aging, physical activity, and diabetic complications related to loss of muscle strength in patients with type 2 diabetes

Abstract: Patients with type 2 diabetes may have motor dysfunctions such as loss of muscle strength. Compared with non-diabetic subjects, patients with diabetes show decreased lower extremity muscle strength. The aim of this review was to describe the influence of factors associated with loss of muscle strength in patients with type 2 diabetes. Aging promotes an accelerated loss of muscle strength in patients with diabetes. Physical inactivity may cause a decline in muscle strength in patients with diabetes. Gradual los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
4
17
0
1
Order By: Relevance
“…Additionally, we found that the presence of micro- and macrovascular complications was higher in patients with physical inactivity. This is in line with a recent review on diabetic polyneuropathy and nephropathy [ 35 ]. Interestingly, diabetic polyneuropathy is associated with lower muscle strength measured by knee extension force [ 25 , 32 , 35 ], providing an alternative cause of muscle mass decline in addition to reduced dietary protein intake.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we found that the presence of micro- and macrovascular complications was higher in patients with physical inactivity. This is in line with a recent review on diabetic polyneuropathy and nephropathy [ 35 ]. Interestingly, diabetic polyneuropathy is associated with lower muscle strength measured by knee extension force [ 25 , 32 , 35 ], providing an alternative cause of muscle mass decline in addition to reduced dietary protein intake.…”
Section: Discussionsupporting
confidence: 92%
“…A Mann-Whitney's U-test, t-test, and χ2 test were used to compare background factors and indices of physical functioning between the two groups with reamputation histories versus groups with no reamputation histories, depending on the data characteristics. Multivariate Cox regression analysis was also performed after adjusting for confounding by inputting sex [2], age [10], serum albumin levels [26], and knee extensor muscle strength [27] as covariates with reference to items that were signi cant in univariate analysis and previous studies to identify factors associated with reamputation. To account for multicollinearity in this process, variables that were considered clinically important were left in the model if the absolute value of the correlation coe cients between the independent variables was greater than 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a systemic disease and MTP joint deformity is likely to be a focal manifestation of multi-system deterioration [8,9]. Neural and motor dysfunction contribute to deficits in muscle strength [10][11][12], fatty infiltration of intrinsic foot muscle [13][14][15], and altered movements during functional tasks that have been correlated to MTP joint hyperextension [16]. In addition to neural and motor dysfunction, the vascular system has a number of DM-related impairments including peripheral artery disease, endothelial dysfunction [17], and blood flow dysregulation from autonomic nervous system dysfunction [18].…”
Section: Introductionmentioning
confidence: 99%